HEALTH SERVICE INNOVATION FOR PEOPLE WITH VISUAL DISABILITIES THROUGH BREXIT IN MALANG CITY - Rosyidatuzzahro Anisykurlillah (Sean Institute, 2022)
To equalize services at all levels of society, the City Government of Malang innovates in health services for the blind. Brexit or Braille e-ticket and extraordinary access for visual disabilities is a form of innovation for persons with disabilities implemented at the Janti Health Center. This study aims to describe and analyze service innovations for persons with disabilities through Brexit in Malang City by looking at the innovation's attributes: relative advantage, compatibility, complexity, trialability, and observability. This study uses a qualitative method with a descriptive approach where data is obtained from interviews and observations and uses interactive model analysis techniques. The results of the study show that the relative advantage attribute provides benefits from an economic aspect. Brexit will reform the health care system for the blind to save resources. The compatibility attribute indicates that it is in accordance with the wishes of the blind because they find it easier to serve. On the complexity attribute, there is no complexity found in the management process during service. Meanwhile, the observability attribute is in accordance with the wishes and needs of persons with disabilities.